Assessing sublimation during snow transport and sublimation effects on the isotopic composition of water vapor ... - Sigmund, Armin (Lausanne, EPFL, 2023)
Sublimation influences the water storage in snow covers and glaciers, which is important for water use and projections of the sea level rise. Yet, it is challenging to quantify sublimation for large areas or in conditions of snow transport. In-situ measurements only provide local information and can be affected by errors in conditions of snow transport. Therefore, models are crucial. Large-scale models suggest that sublimation of drifting and blowing snow is a relevant term in the surface mass balance of the Antarctic Ice Sheet but the uncertainties are large because the underlying processes are strongly simplified. On the contrary, small-scale models such as large-eddy simulation (LES) with Lagrangian particles represent these processes with a high level of detail and provide unique insights. Indirect information on sublimation can be obtained by measuring stable water isotopes (SWIs) as their relative abundance is influenced by phase changes. Yet, SWIs have so far only provided qualitative insights in the ...